SAT0280 Prolonged Risk of Specific Malignancies following Cyclophosphamide-Therapy among Patients with Granulomatosis with Polyangiitis (WEGENER'S). (10th June 2014) - Faurschou, M.; Mellemkjaer, L.; Voss, A.; Keller, K.K.; Hansen, I.T.; Baslund, B.
Abstract : Background: The long-term cancer-risk of patients treated for granulomatosis with polyangiitis (Wegener's; GPA) is not well characterized. Objectives: We assessed the risk of early and late-occurring cancers among 293 patients diagnosed with GPA during 1973-1999 and followed throughout 2010. Methods: The cancer-incidence in the cohort was determined by linkage with the Danish Cancer Registry and compared to that in the general population by calculation of standardized incidence ratios (SIRs). Results: The median duration of follow-up was 9.7 (range: 0-36) years. 73 cancers occurred, of which 30 were non-melanoma skin cancers (NMSC) and 11 were bladder carcinomas. A high occurrence of NMSC was observed from the second year of follow-up onwards, with a SIR of 7.0 (95% CI: 2.3-16) for cases diagnosed ≥20 years after GPA. The incidence of bladder cancer was increased after 5-9, 10-14, and 15-19 years of follow-up, with SIR estimates for these latency-periods of 5.3 (95% CI: 1.1-15), 14.4 (95% CI: 5.3-31), and 10.5 (95% CI: 1.2-38), respectively. The incidence of myeloid leukemia was significantly increased during year 5-9 (SIR: 23.9 (95% CI: 2.7-86)). Increased incidence of NMSC, bladder cancer, and myeloid leukemia was observed among patients exposed to cumulative cyclophosphamide-doses >36 gram, while the only malignancy-type observed in excess among those treated with lower cyclophosphamide-doses was NMSC. The cancer-risk among cyclophosphamide-naïve patients was not significantly increased. Conclusions: GPA patients experience a greater-than-expected number of cancers following conventional therapies, including an increased number of very late-occurring malignancies. The risk of specific cancer-types rises with the cumulative cyclophosphamide-dose administered. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5439